Teachers’ Perceptions of The Importance of Parenting Programs in Schools - Rohmah, Ni'matur; Fadjryana Fitroh, Siti; Oktavianingsih, Eka; Rizki Tiara, Dinda (Al-Athfal: Jurnal Pendidikan Anak, 2022)
Purpose – This study aims to describe teachers’ perceptions on the importance of parenting programs in Play Groups or Kindergarten schools in Kamal District, Bangkalan.Design/methods/approach – The descriptive quantitative method is used. The sampling technique used is purposive sampling with the total population being all teachers at Play Group or Kindergarten schools in Kamal District, Bangkalan. The number of research samples are 35 teachers. The collecting data used is a questionnaire.Findings – The results of this study show that teachers’ perceptions on the importance of parenting programs in Play Groups or Kindergarten schools in Kamal District, Bangkalan, have the highest score in the important middle category by 48%.Research implications/limitations – This study has limitation on one independent variable, namely the teacher’s perception variable about the importance of parenting programs in schools. Practical implications – This study shows that the teachers still do not fully have a critical perception on parenting programs, and teachers have less interest in holding parenting programs in schools even though they have knowledge about parenting programs and know the benefits.Originality/value – This study hoped the teacher could move and accommodate parents to hold a parenting program in schools with teachers who have a good perception on the programs.Paper type Research paper